POLITENESS STRATEGIES IN THE CHARACTERS’ APOLOGIES IN THE WHALE MOVIE - Sari, Dewi Purnama; Asia, Zona; Kurniawan, Ferry; Syaputri, Komala Dwi (Universitas Muhammadiyah Palembang, 2026)
This study aims to analysed politeness strategies in apology expressions in The Whale (2022). This research applied a qualitative method through case study design to explore how characters use language to convey apologies in different social and emotional contexts. The data were collected from documents with selected dialogues in the film containing apology expressions, which were then carefully examined and categorized. The researcher analysed the data based on Leech's politeness maxims, focusing on how each maxim is reflected in the characters’ speech. The results show that the tact maxim is the most dominant strategy, followed by sympathy, approbation, and modesty maxims. These findings suggest that characters tend to minimize harm and show concern for others when apologizing. Furthermore, the study indicates that apology strategies play an important role in maintaining interpersonal relationships, expressing emotional conditions, and revealing deeper psychological states among characters in the film.